2020
DOI: 10.1007/s00344-020-10246-6
|View full text |Cite
|
Sign up to set email alerts
|

Co-regulation Role of Endogenous Hormones and Transcriptomics Profiling Under Cold Stress in Tetrastigma hemsleyanum

Abstract: Background: Tetrastigma hemsleyanum Diels et Gilg is a valuable medicinal herb, Chilling sensitivity is the dominant environmental factor limiting the artificial domestication of the plant. Hormonerelated gene regulation and hormone signaling pathways in response to cold stress in T. hemsleyanum remain unknown. Results: Some key genes involved in hormones biosynthesis, such as ZEP and NCED genes of ABA biosynthesis, GA2ox, GA3ox, and GA20ox genes of GA biosynthesis, ACO genes of ET biosynthesis pathway were sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…The 9-cis epoxycarotenoid dioxygenase (NCED) is considered to be a key rate-limiting enzyme in ABA biosynthesis ( González-Silva et al., 2011 ); previous research has shown that cold stress caused significant upregulation of NCED s at 24 h in T. hemsleyanum ( Peng et al., 2021 ). However, in this research study, two out of three NCEDs were suppressed by cold, and one out of three NCEDs were only significantly induced in FS.…”
Section: Discussionmentioning
confidence: 99%
“…The 9-cis epoxycarotenoid dioxygenase (NCED) is considered to be a key rate-limiting enzyme in ABA biosynthesis ( González-Silva et al., 2011 ); previous research has shown that cold stress caused significant upregulation of NCED s at 24 h in T. hemsleyanum ( Peng et al., 2021 ). However, in this research study, two out of three NCEDs were suppressed by cold, and one out of three NCEDs were only significantly induced in FS.…”
Section: Discussionmentioning
confidence: 99%
“…RNA extraction, quantification, and transcriptome sequencing were carried out according to our previous method ( Peng et al, 2019 , 2021 ). We used NEBNext ® Ultra™ RNA Library Prep Kit for Illumina ® (NEB, United States) to generate sequencing libraries.…”
Section: Methodsmentioning
confidence: 99%
“…Cold treatment induces many biochemical pathways, including glucose metabolism [ 7 ] and amino acid metabolism [ 8 ], which are important for the synthesis of not only proteins but also precursors of various metabolites and metabolic products with multiple functions in plant responses to cold. Furthermore, studies have revealed that the regulation of plant hormones, including abscisic acid (ABA) [ 9 , 10 ], gibberellic acid (GA) [ 11 ], and jasmonic acid (JA) [ 12 ], changes during cold stress.…”
Section: Backgroundsmentioning
confidence: 99%